2018
DOI: 10.1007/s12024-018-9994-6
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of decontamination procedures used in forensic hair analysis

Abstract: Hair is a mainstream specimen used in forensic toxicology to determine drug use and exposure. However, the interpretation of an analytical hair result can be complicated by the presence of external drug contamination. Decontamination procedures are included in hair analysis methods to remove external contamination, but the capacity of these washes to completely remove contamination for all drugs is controversial. It is evident that there is no consensus on the most effective decontamination procedure, nor can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 60 publications
0
15
0
1
Order By: Relevance
“…It is known that the keratinized hair shaft has a complex, multi-compartment structure and the drug incorporation in hair is a function of the acidity/basicity of the compound, its lipophilicity, and its affinity to melanin [ 72 ]. On the other hand, the main factors that influence drug incorporation in hair, affect the drug extraction from hair, as well [ 73 ]. Therefore, the extraction procedure poses several issues most relevant to the complexity of this matrix.…”
Section: Aspects Of Nps Hair Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that the keratinized hair shaft has a complex, multi-compartment structure and the drug incorporation in hair is a function of the acidity/basicity of the compound, its lipophilicity, and its affinity to melanin [ 72 ]. On the other hand, the main factors that influence drug incorporation in hair, affect the drug extraction from hair, as well [ 73 ]. Therefore, the extraction procedure poses several issues most relevant to the complexity of this matrix.…”
Section: Aspects Of Nps Hair Extractionmentioning
confidence: 99%
“…Of main concern to the toxicologists is the removal of the external contaminations from hair, consisting of organic and inorganic chemicals that have been deposited to the hair shafts, by applying appropriate washing steps. The hair washing steps are usually applied according to the suggested guidelines which states further that external contamination must be considered to interpret findings, while researchers should evaluate the efficiency of washing procedures [ 73 , 74 ]. Nevertheless, some of the reviewed studies herein, reported extensive washing procedures, and others none, indicating the different viewpoints for the necessity of this step, especially in respect to differentiate the active drug use from external drug deposition onto hair.…”
Section: Aspects Of Nps Hair Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Society of Hair Testing recommends that a hair decontamination procedure should include both an organic and aqueous washing step. Studies have shown that the most effective organic solvent was methanol and the most effective aqueous solvent contained sodium dodecyl sulfate detergent (Mantinieks et al 2018).…”
Section: Washing/decontamination Proceduresmentioning
confidence: 99%
“…Before sample extraction, a decontamination procedure is recommended to be performed in a washing step that includes both an organic and an aqueous phase. In that way, any external contaminant, which could lead to a false‐positive result, must be washed away, without removing the target analytes 10 . The next step in sample preparation is the homogenization with the aim of increasing the surface area exposed to the extraction agents, usually executed by cutting hair into small pieces or by grinding, for example, in a ball or cryogenic mill 11 .…”
Section: Introductionmentioning
confidence: 99%